Method for preparing ablation-resistant copper alloy through blue laser cladding process and ablation-resistant copper alloy

The blue laser cladding process forms a cladding layer on the copper substrate, which solves the problem of insufficient laser absorption of copper alloy materials under high reflectivity, and achieves the preparation and performance improvement of large-scale ablation-resistant copper alloys, meeting the arc ablation requirements under harsh service conditions.

CN120465000APending Publication Date: 2025-08-12HENAN UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510419425.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2025-08-12

AI Technical Summary

Technical Problem

The prior art is difficult to achieve effective laser absorption on copper and copper alloy materials with high reflectivity and high thermal conductivity, making it difficult to prepare large-scale ablation-resistant copper alloys, and traditional methods are difficult to meet the arc ablation resistance requirements of copper alloys under harsh service conditions.

Method used

The blue light laser cladding process is adopted, and the mixed powder is prepared by ball milling by using the high absorption rate of copper material to form a cladding layer on the copper substrate. Combined with appropriate laser process parameters and protective gas, the melting and rapid cooling of the powder material is achieved to form an excellent cladding layer.

Benefits of technology

A high-performance clad layer is formed on the surface of the copper substrate, which improves the ablation resistance of the copper alloy while maintaining excellent conductivity and thermal conductivity, solves the problem of preparation of large-scale copper alloys, and improves the overall performance of the copper substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120465000A_ABST
    Figure CN120465000A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of laser cladding processing, and provides a method for preparing an ablation-resistant copper alloy through a blue laser cladding process and the ablation-resistant copper alloy. The method comprises the following steps that alloy powder is subjected to ball milling, and mixed powder is obtained; the alloy powder is CuCr powder, CuW powder, ODS-Cu powder, SiO2 / Cu powder or C / Cu powder; and the mixed powder is used for preparing a cladding layer on a copper base material by adopting a blue laser cladding process. According to the method, the characteristic that a copper material is high in blue laser absorptivity is utilized, the problems of heat input accumulation, air holes, inclusions and the like under the conditions of low absorptivity and high energy density are avoided, and laser process parameters are controlled to form a molten pool on the surface of a copper base material; and the coaxial powder feeding device gathers the powder material into the molten pool for melting and rapid cooling and solidification by utilizing protective gas to form a cladding layer with excellent performance, so that the surface of the copper base material is modified, and the performance of the copper base material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of laser cladding processing, and in particular to a method for preparing an ablation-resistant copper alloy by a blue laser cladding process and the ablation-resistant copper alloy. Background Art

[0002] Copper and copper alloy materials have excellent conductivity (electrical / thermal conductivity) and mechanical properties. They have extensive application value in key national industries and extreme manufacturing fields such as aerospace, 5G communications, high-speed railways, power equipment, electronic information, new energy vehicles, and national defense and military industry, and play an important role in national economic and social development and national strategic security. In recent years, with the rapid development of the above fields, the comprehensive performance requirements for copper and copper alloy materials have become increasingly higher. For example: (1) In the high-speed railway bow-net system, as my country's railways develop towards high-speed, heavy-load and other harsh service conditions, the conduction current of power lines / slide plates and return blocks has increased from the traditional 200A to more than 600A, and the energy transmission density has increased by 3 times, which puts higher requirements on the arc erosion resistance and offline rate of the friction pair. (2) In the high-voltage switchgear industry, as the transmission voltage of my country's backbone power grid develops from high voltage (100-300kV) to ultra-high voltage (750-1000kV) and ultra-high voltage (≥1000kV), the energy transmission density of various high-voltage switches will increase by more than 1 times; for various contacts, after the size is reduced, especially under sealing conditions, the heat capacity and heat transfer conditions of the contact area will deteriorate significantly, resulting in a significant increase in the operating temperature of the material, and the effects of oxidation and material performance degradation on the conductive properties and electrical contact properties will become more prominent.

[0003] The above-mentioned fields require that copper and copper alloy materials must maintain good friction contact and electrical contact at the same time under harsh conditions such as high temperature, high pressure, and high current. Copper and copper alloy materials are required to have not only good mechanical properties and conductive properties, but also excellent arc erosion resistance under harsh service conditions. Currently, the commonly used copper-based materials in the above-mentioned fields include copper alloys (CuCr, CuW, CuBe, ODS-Cu), copper-based composite materials (Al2O3 / Cu, SiO2 / Cu, SiC / Cu, TiB2 / Cu, C / Cu), etc. The commonly used preparation methods for the above-mentioned materials include powder metallurgy, infiltration, and vacuum arc melting. However, due to equipment limitations, it is difficult to achieve the production of large-scale billets.

[0004] Because the process uses pure copper or copper alloy as the substrate and CuCr, CuW, ODS-Cu, SiO2 / Cu, C / Cu alloy mixed powders as the cladding material, copper and copper alloys have high reflectivity and high thermal conductivity, and their absorption rate in the infrared range is extremely poor, less than 6%. Therefore, providing a method for preparing large-scale ablation-resistant copper alloys by blue laser cladding is of great significance. Summary of the Invention

[0005] The purpose of the present invention is to provide a method for preparing an ablation-resistant copper alloy by a blue laser cladding process and the ablation-resistant copper alloy in order to overcome the deficiencies of the prior art.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing an ablation-resistant copper alloy by a blue-light laser cladding process, comprising the following steps:

[0008] 1) ball milling the alloy powder to obtain a mixed powder; the alloy powder is CuCr powder, CuW powder, ODS-Cu powder, SiO2 / Cu powder or C / Cu powder;

[0009] 2) The mixed powder is used to prepare a cladding layer on a copper substrate using a blue light laser cladding process to obtain an ablation-resistant copper alloy.

[0010] Preferably, the medium for ball milling in step 1) is agate balls, and the mass ratio of alloy powder to agate balls is 4 to 6:1.

[0011] Preferably, the ball milling time in step 1) is 7 to 9 hours, and the rotation speed is 80 to 100 r / min.

[0012] Preferably, the particle size of the mixed powder in step 1) is 45 to 50 μm.

[0013] Preferably, in the blue light laser cladding process in step 2), the powder feeding amount of the mixed powder is 8 to 10 g / min, the powder feeding gas flow rate is 9 to 11 L / min; the shielding gas flow rate is 9 to 11 L / min, and argon is used to protect the molten pool during the blue light laser cladding process.

[0014] Preferably, in the blue laser cladding process in step 2), the blue laser output power is 1500-2000W, the scanning speed is 6-10mm / s, the spot diameter is 2mm, the overlap rate of single-pass cladding and multi-pass overlapping cladding is 40-50%.

[0015] Preferably, the copper substrate in step 2) is pure copper or a copper alloy; the copper substrate is a copper substrate that has been polished and cleaned in sequence, and the cleaning agent is acetone.

[0016] The invention also provides an ablation-resistant copper alloy prepared by the method.

[0017] The beneficial effects of the present invention include the following:

[0018] 1) The present invention utilizes the high absorption rate of copper materials for blue lasers to avoid problems such as heat input accumulation, pores, and inclusions under low absorption rate and high energy density conditions. Appropriate laser process parameters are used to form a molten pool on the surface of the copper substrate. A coaxial powder feeding device uses a protective gas to gather the powder material into the molten pool for melting and rapid cooling and solidification to form a cladding layer with excellent performance, thereby modifying the surface of the copper substrate and improving the performance of the copper substrate.

[0019] 2) The present invention overcomes the problem that traditional preparation methods are difficult to prepare large-scale ablation-resistant copper alloys. While ensuring the excellent electrical conductivity and thermal conductivity of the copper alloy, the ablation resistance of the copper substrate surface is improved. The cladding layer of the present invention is a copper alloy or a copper-based composite material, which has similar physical parameters to the substrate pure copper, good affinity, and is metallurgically bonded to the copper substrate with high bonding strength. The method of the present invention can clad different materials on the surface of the copper substrate to obtain a gradient alloy layer, which can be used to clad gradient composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a picture of the copper-chromium cladding layer processed by blue light laser cladding on the pure copper substrate of Example 1. DETAILED DESCRIPTION

[0021] The present invention provides a method for preparing an ablation-resistant copper alloy by a blue-light laser cladding process, comprising the following steps:

[0022] 1) ball milling the alloy powder to obtain a mixed powder; the alloy powder is CuCr powder, CuW powder, ODS-Cu powder, SiO2 / Cu powder or C / Cu powder;

[0023] 2) The mixed powder is used to prepare a cladding layer on a copper substrate using a blue light laser cladding process to obtain an ablation-resistant copper alloy.

[0024] In the present invention, the medium for ball milling in step 1) is preferably agate balls, and the mass ratio of alloy powder to agate balls is preferably 4-6:1, more preferably 4.5-5.5:1, and more preferably 5:1.

[0025] In the present invention, the ball milling time in step 1) is preferably 7 to 9 hours, more preferably 7.5 to 8.5 hours, and more preferably 8 hours, and the ball milling speed is preferably 80 to 100 r / min, more preferably 85 to 95 r / min, and more preferably 90 r / min.

[0026] In the present invention, the particle size of the mixed powder in step 1) is preferably 45 to 50 μm, more preferably 47 to 48 μm.

[0027] In the present invention, in the blue light laser cladding process described in step 2), the powder feeding amount of the mixed powder is preferably 8-10 g / min, more preferably 8.5-9.5 g / min, more preferably 9 g / min, and the powder feeding gas flow rate is preferably 9-11 L / min, more preferably 9.5-10.5 L / min, more preferably 10 L / min; the shielding gas flow rate is preferably 9-11 L / min, more preferably 9.5-10.5 L / min, more preferably 10 L / min, and argon is preferably used to protect the molten pool during the blue light laser cladding process.

[0028] In the present invention, in the blue light laser cladding process described in step 2), the output power of the blue light laser is preferably 1500-2000 W, more preferably 1600-1900 W, more preferably 1700-1800 W, the scanning speed is preferably 6-10 mm / s, more preferably 7-9 mm / s, more preferably 8 mm / s, the spot diameter is preferably 2 mm, and the overlap rate of single-pass cladding and multi-pass overlapping cladding is preferably 40-50%, more preferably 43-48%, and more preferably 45-46%.

[0029] In the present invention, the equipment for the laser cladding process is an HLAAM10 red / blue laser-CMT arc composite laser.

[0030] In the present invention, the copper substrate in step 2) is preferably pure copper or a copper alloy; the copper substrate is preferably a copper substrate that has been polished and cleaned in sequence, and the cleaning agent is preferably acetone.

[0031] In the present invention, the surface to be processed of the copper substrate is polished with sandpaper to remove surface oxides, and is cleaned and wiped with acetone to achieve the purpose of degreasing, thereby ensuring that the part to be clad on the copper substrate is fully clean.

[0032] In the present invention, the cladding layer is ground and polished, preferably to a thickness of 0.5 to 1 mm, more preferably to 0.6 to 0.8 mm, and then polished to a flat and smooth surface.

[0033] The invention also provides an ablation-resistant copper alloy prepared by the method.

[0034] The technical solutions provided by the present invention are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0035] In the embodiment, the copper substrate is a pure copper plate having a thickness of 10 mm, a length of 100 mm, and a width of 45 mm; the equipment for the laser cladding process is an HLAAM10 red / blue laser-CMT arc composite laser;

[0036] Among the agate balls, the mass ratio of 12.25g agate balls, 5.25g agate balls and 0.25g agate balls is 1:3:6.

[0037] Example 1

[0038] The surface of the pure copper plate is polished with sandpaper, and then cleaned and wiped with acetone to obtain a clean pure copper plate at the part to be clad.

[0039] Copper powder and chromium powder were mixed in a mass ratio of 1:1, and the obtained powder and agate balls were mixed in a mass ratio of 5:1. The powder was ball-milled in a GMS5-4 jar mill for 8 hours at a ball mill speed of 90 r / min to obtain a mixed powder with a particle size of 48 μm. The mixed powder was poured into an AJG-L60 double-drum powder feeder.

[0040] Clean pure copper sheets were subjected to a blue laser cladding process using an arc hybrid laser under argon protection. The process parameters were: a blue laser power of 1600W, a mixed powder feed rate of 9g / min, a powder feed gas flow rate of 10L / min, a shielding gas flow rate of 10L / min, a scanning speed of 6mm / s, a spot diameter of 2mm, a single-pass cladding process, and a cladding overlap ratio of 45%. Argon was used to protect the molten pool during the cladding process, resulting in a copper-chromium alloy cladding layer on the surface of the pure copper sheet. The copper-chromium alloy cladding layer was ground to a thickness of 0.6mm and then polished to a smooth surface.

[0041] The copper-chromium alloy cladding layer on the surface of the pure copper plate of this embodiment not only enables the core to maintain the excellent electrical conductivity of pure copper, but also provides the surface with the comprehensive properties of CuCr alloy such as high current breaking capacity, high voltage bearing capacity, and good anti-welding performance.

[0042] Example 2

[0043] The surface of the pure copper plate is polished with sandpaper, and then cleaned and wiped with acetone to obtain a clean pure copper plate at the part to be clad.

[0044] Copper powder and chromium powder were mixed in a mass ratio of 1:1, and the obtained powder and agate balls were mixed in a mass ratio of 5:1. The powder was ball-milled in a GMS5-4 jar mill for 8 hours at a ball mill speed of 90 r / min to obtain a mixed powder with a particle size of 48 μm. The mixed powder was poured into an AJG-L60 double-drum powder feeder.

[0045] Clean pure copper sheets were subjected to a blue laser cladding process using an arc hybrid laser under argon protection. The process parameters were: 1800W blue laser power, 9g / min mixed powder feed, 10L / min powder feed gas flow, 10L / min shielding gas flow, 8mm / s scanning speed, 2mm spot diameter, single-pass cladding, and a 47% overlap. Argon was used to protect the molten pool during the cladding process, resulting in a copper-chromium alloy cladding layer on the surface of the pure copper sheet. The copper-chromium alloy cladding layer was ground to a thickness of 0.8mm and then polished to a smooth surface.

[0046] Example 3

[0047] The surface of the pure copper plate is polished with sandpaper, and then cleaned and wiped with acetone to obtain a clean pure copper plate at the part to be clad.

[0048] Copper powder and tungsten powder were mixed in a mass ratio of 1:1, and the obtained powder and agate balls were mixed in a mass ratio of 4.5:1. The powder was ball-milled in a GMS5-4 jar mill for 7.5 h at a speed of 95 r / min to obtain a mixed powder with a particle size of 46 μm. The mixed powder was poured into an AJG-L60 double-drum powder feeder.

[0049] Clean pure copper sheets were subjected to a blue laser cladding process using an arc hybrid laser and argon protection. The process parameters were: 1800W blue laser power, 8.5g / min mixed powder feed, 9.5L / min powder feed gas flow, 9.5L / min shielding gas flow, 8mm / s scanning speed, 2mm spot diameter, single-pass cladding, 46% overlap, and argon gas protection for the molten pool. A copper-tungsten alloy cladding layer was formed on the surface of the pure copper sheet. The copper-tungsten alloy cladding layer was ground to a thickness of 1mm and then polished to a smooth surface.

[0050] Example 4

[0051] The surface of the pure copper plate is polished with sandpaper, and then cleaned and wiped with acetone to obtain a clean pure copper plate at the part to be clad.

[0052] Copper powder and carbon powder were mixed in a mass ratio of 1:1, and the obtained powder and agate balls were mixed in a mass ratio of 5.5:1. The powder was ball-milled in a GMS5-4 jar mill for 8.5 h at a speed of 85 r / min to obtain a mixed powder with a particle size of 49 μm. The mixed powder was poured into an AJG-L60 double-drum powder feeder.

[0053] A clean pure copper sheet was placed on an arc hybrid laser under argon protection and subjected to a blue laser cladding process. The process parameters were: 2000W blue laser power, 9.5g / min mixed powder feed, 10.5L / min powder feed gas flow, 10.5L / min shielding gas flow, 10.5L / min shielding gas flow, 10mm / s scanning speed, 2mm spot diameter, single-pass cladding, 43% overlap, and argon gas protection for the molten pool. A copper-carbon composite material was formed on the surface of the pure copper sheet. The copper-carbon composite cladding layer was ground to a thickness of 0.5mm and then polished to a smooth surface.

[0054] The present invention uses pure copper or copper alloy as the substrate, and mixed powders of CuCr, CuW, oxide dispersion strengthened copper alloy (ODS-Cu), SiO2 / Cu, C / Cu, etc. as the cladding material. Since copper and copper alloys are materials with high reflectivity and high thermal conductivity, their absorption rate of laser in the infrared band is extremely poor, with an absorption rate of less than 6%. Therefore, a blue light laser cladding method is used to melt the above powders onto the surface of the pure copper / copper alloy substrate under argon protection, thereby obtaining a surface ablation-resistant layer, thereby improving the ablation resistance of the copper / copper alloy surface layer, and preparing large-scale ablation-resistant copper alloys.

[0055] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing ablation-resistant copper alloy by blue laser cladding process, characterized in that: The following steps are included: 1) ball milling the alloy powder to obtain a mixed powder; the alloy powder is CuCr powder, CuW powder, ODS-Cu powder, SiO2 / Cu powder or C / Cu powder; 2) The mixed powder is used to prepare a cladding layer on a copper substrate using a blue light laser cladding process to obtain an ablation-resistant copper alloy.

2. The method according to claim 1, characterized in that Step 1) The ball milling medium is agate balls, and the mass ratio of alloy powder to agate balls is 4 to 6:

1.

3. The method according to claim 1 or 2, characterized in that The ball milling time in step 1) is 7 to 9 hours, and the rotation speed is 80 to 100 r / min.

4. The method according to claim 3, characterized in that Step 1) The particle size of the mixed powder is 45 to 50 μm.

5. The method according to claim 1 or 4, characterized in that In the blue light laser cladding process of step 2), the powder feeding rate of the mixed powder is 8-10 g / min, the powder feeding gas flow rate is 9-11 L / min; the shielding gas flow rate is 9-11 L / min, and argon gas is used to protect the molten pool during the blue light laser cladding process.

6. The method according to claim 5, characterized in that In the blue laser cladding process of step 2), the output power of the blue laser is 1500-2000W, the scanning speed is 6-10mm / s, the spot diameter is 2mm, the overlap rate of single-pass cladding and multi-pass overlapping cladding is 40-50%.

7. The method according to claim 6, characterized in that In step 2), the copper substrate is pure copper or a copper alloy; the copper substrate is a copper substrate that has been polished and cleaned in sequence, and the cleaning agent is acetone.

8. The ablation-resistant copper alloy prepared by the method according to any one of claims 1 to 7.

Citation Information

Cited By

  • High-elasticity ablation-resistant beryllium copper alloy for high-voltage switch and preparation method of high-elasticity ablation-resistant beryllium copper alloy

    CN122256750A